Measurable residual disease monitoring by NGS before allogeneic hematopoietic cell transplantation in AML - Thol, Felicitas; Schlenk, Richard Friedrich (Blood, 2018)
Visual Abstract - Download figureOpen in new tabDownload powerpoint - - Molecular measurable residual disease (MRD) assessment is not established in approximately 60% of acute myeloid leukemia (AML) patients because of the lack of suitable markers for quantitative real-time polymerase chain reaction. To overcome this limitation, we established an error-corrected next-generation sequencing (NGS) MRD approach that can be applied to any somatic gene mutation. The clinical significance of this approach was evaluated in 116 AML patients undergoing allogeneic hematopoietic cell transplantation (alloHCT) in complete morphologic remission (CR). Targeted resequencing at the time of diagnosis identified a suitable mutation in 93% of the patients, covering 24 different genes. MRD was measured in CR samples from peripheral blood or bone marrow before alloHCT and identified 12 patients with persistence of an ancestral clone (variant allele frequency [VAF] >5%). The remaining 96 patients formed the final cohort of which 45% were MRD+ (median VAF, 0.33%; range, 0.016%-4.91%). In competing risk analysis, cumulative incidence of relapse (CIR) was higher in MRD+ than in MRD− patients (hazard ratio [HR], 5.58; P < .001; 5-year CIR, 66% vs 17%), whereas nonrelapse mortality was not significantly different (HR, 0.60; P = .47). In multivariate analysis, MRD positivity was an independent negative predictor of CIR (HR, 5.68; P < .001), in addition to FLT3-ITD and NPM1 mutation status at the time of diagnosis, and of overall survival (HR, 3.0; P = .004), in addition to conditioning regimen and TP53 and KRAS mutation status. In conclusion, NGS-based MRD is widely applicable to AML patients, is highly predictive of relapse and survival, and may help refine transplantation and posttransplantation management in AML patients.
Gesehen am 06.08.2019